Co-gasification reactivity and kinetics of municipality and coffee waste residue hydrochar and South African density separated coal blends. (December 2021) - Uwaoma, R.C.; Strydom, C.A.; Bunt, J.R.; Matjie, R.H.; Okolo, G.N.; Marx, S.
Abstract: Residues obtained from hydrothermal liquefaction of municipality waste (MSWR) and coffee waste (CR) were blended with coal and charred at 1000 °C. Co-gasification experiments were conducted on the coal, MSWR, CR, and their respective blended chars using a thermogravimetric analyser. The reactivities of the char samples decreased in the order: MSWR > CR > MSWR-coal blend > CR-coal blend > coal. RPM was found to best predict the reaction profile of the coal, and the blended chars, except for the MSWR and CR chars, which fitted satisfactorily upon the application of the MRPM. The activation energies obtained using the RPM, MRPM, and the different reactivity models showed that the MSWR, CR, and the blend chars have lower activation energies when compared to the feed coal char. Although the MSWR and CR exhibited catalytic influence on the coal char during co-gasification, the synergistic effect was inhibitory with all determined SE < 1. Graphical abstract: Unlabelled Image Highlights: Municipality and coffee waste HTL residue chars have higher gasification reactivities than coal. Blends of the waste and coal chars resulted in a reduction in the gasification activation energies. The RPM fitted the gasification data of the coal and blended samples. The MRPM best describes the waste residue chars gasification data. A synergistic effect of <1 was observed for the gasification of the blended samples.